Pendampingan Tata Kelola Badan Usaha Milik Desa (BUMDes) Katon Margo Sembada Berbasis Teknologi Informasi dan Komunikasi - Sakir, Sakir; Astuti, Laras; Muttaqien, Muhammad; Mutiarin, Dyah (Universitas Muhammadiyah Semarang, 2021)
The BUMDes of Katon Margo Sembada is one of the BUMDes affected during the covid-19 pandemic. This impact can be seen from the decrease in income by 30%. This happens because so far BUMDES Katon Margo Sembada, still uses conventional methods in marketing. There is no website or social media related to the BUMDES business unit of Katon Margo Sembada, making this BUMDES undeveloped and unknown to many people. In addition, BUMDES Katon Margo Sembada also lacks human resources who can manage BUMDES well through the marketplace and digital marketing. Furthermore, this community service aims to aid BUMDES Katon Margo Sembada based on technology, information, and communication so that the managed business units can be known by the wider community. Through the community empowerment approach, this service is expected to change the existence of the community to be more independent, productive, and prosperous. Based on the results of the initial assessment of the problem, the team has aided in website creation, social media, mentoring and training in media, digital marketing, and marketplace. In addition, the team also initiated by establishing strategic collaboration between BUMDES Katon Margo Sembada and the Government Science Laboratory, University of Muhammadiyah Yogyakarta in the implementation of Information and Communication Technology-Based Management and Assistance.